Epidemiological Findings and Clinical and Magnetic Resonance Presentations in Subacute Sclerosing Panencephalitis - İŞCAN, AKIN; Cece, H.; Tokay, L.; Yildiz, S.; KARAKAS, O.; KARAKAS, E.; Iscan, AKIN (My University, 2011)
Subacute sclerosing panencephalitis (SSPE) is a rare, progressive, inflammatory neurodegenerative disease. This study investigated the relationships of clinical stage with epidemiological and magnetic resonance imaging (MRI) findings in SSPE by retrospective review of 76 cases (57 male) diagnosed by typical periodic electroencephalographic features, clinical symptoms and elevated measles antibody titre in cerebrospinal fluid. Clinical stage at diagnosis was I or II in 48 patients, III in 25 and IV in three. Prominent findings at presentation were atonic/myoclonic seizures (57.9%) and mental deterioration with behaviour alteration (30.3%). Frequent MRI findings (13 - 32 patients) were subcortical, periventricular and cortical involvement and brain atrophy; the corpus callosum, basal ganglia, cerebellum and brainstem were less frequently involved. Five patients had pseudotumour cerebri. Cranial MRI at initial diagnosis was normal in 21 patients (19 stage I/II, two stage III/IV). Abnormal MRI findings were significantly more frequent in the later stages, thus a normal initial cranial MRI does not exclude SSPE, which should, therefore, be kept in mind in childhood demyelinating diseases even when the presentation is unusual.